PENGARUH DIVERSITAS GENDER DEWAN DIREKSI DAN UKURAN DEWAN DIREKSI TERHADAP PENGHINDARAN PAJAK (Studi Empiris Pada Perusahaan Perbankan Yang Terdaftar Di BEI Tahun 2014-2018) - Nisrina Nuril Mala; Moh Didik Ardiyanto (Diponegoro Journal of Accounting, 2021)
This study aims to examine the effect of board gender diversity and board size on corporate tax avoidance. The dependent variable of tax avoidance is measured by the effective tax rate (ETR), while the independent variables of board gender diversity and board size are measured by dummy variables and the number of board members in five years, respectively. This study also uses control variables consisting of leverage, return on assets, capital intensity, and company age (age).The population in this study are banking sector companies listed on the Indonesia Stock Exchange (BEI) in 2014-2018. This study used a purposive sampling method and obtained 65 samples. This study uses multivariate regression analysis for hypotheses testing. The results of the analysis show that gender diversity of company boards as measured by the presence of female members on the company's board of directors has a positive and insignificant effect on tax avoidance. This study also shows that board size has a negative and insignificant effect on tax avoidance.